Sudden Death Due to Acute Hemorrhagic Pancreatitis: A Case Report (Indian Journal of Forensic Medicine & Toxicology, 2023)
Sudden unexpected deaths pose a challenge for the forensic pathologists. Usually relates to cardiovascular causeand such deaths due to gastrointestinal related pathology are uncommon. Acute pancreatitis is a major etiology ofgastrointestinal sudden deaths. It is mainly associated with gallbladder stones and alcoholism. We report a caseof a 48-year-old man, chronic alcoholic, who was brought dead to hospital after complaints of abdominal painand vomiting. The postmortem examination revealed the death due to acute hemorrhagic pancreatitis. Literatureshows pancreatitis to be significantly associated with alcoholic liver disease. The present case reemphasizes theimportance of examination of retroperitoneal space during autopsy and how ancillary investigations such ashistopathology, chemical analysis, measuring serum amylase, lipase and vitreous glucose levels help in arrivingat final diagnosis.
Keywords: Sudden death, Pancreatic haemorrhage, Pancreatic necrosis, Alcoholic liver disease, Acute hemorrhagic pancreatitis